(untitled) (Journal of Health, Population and Nutrition, 2010)
A community-based, cross-sectional descriptive study was conducted during June-July 2008 to assess the infant- and young child-feeding (IYCF) practices in Bankura district, West Bengal, India. In total, 647 children aged less than two years selected through revised 40-cluster sampling using the indicators of the Integrated Management of Neonatal and Childhood Illness (IMNCI) and World Health Organization. The proportions of infants with early initiation of breastfeeding (13.6%) and exclusive breastfeeding under six months (57.1%) and infants who received complementary feeding at the age of 6-8 months (55.7%) were low. Appropriate feeding as per the IMNCI protocol was significantly less among infants aged 6-11 months (15.2%) and children aged 12-23 months (8.7%) compared to infants aged less than six months (57.1%), which could be attributable to low frequency and amount of complementary feeding. The main problems revealed from the study were late initiation of breastfeeding, low rates of exclusive breastfeeding, and inappropriate complementary feeding practices. Key words: Breastfeeding; Child-feeding practices; Cross-sectional studies; Descriptive studies; Exclusive breastfeeding; Infant-feeding practices; India DOI: 10.3329/jhpn.v28i3.5559 J HEALTH POPUL NUTR 2010 Jun;28(3):294-299